Assessment of Disease Severity in Psoriasis Patients Attending in a Tertiary Care Hospital - Sultana, S; Bhuiyan, MMA; Yesmin, MS; Hossain, S; Zaman, KMS; Akhter , A; Badiuzzaman, S; Sultana, T (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Psoriasis is an immune mediated inflammatory skin disease affecting approximately 2% -3% of the world's population, a worldwide disease, varies in its clinical profile and epidemiology in different regions of the world. Recurrence of the disease is high and severity of psoriasis ranges clinically from mild, moderate and severe. Psoriasis area and severity index (PASI) is a commonly used tool to assess the disease severity of patients. Objective: The purpose of this study was to assess the disease severity of psoriasis patients in a tertiary care hospital. Methodology: This cross-sectional study was conducted in the Department of Laboratory Medicine and Department of Dermatology and Venereology, BSMMU. Duration of the study was from March 2019 to February 2020. Diagnosed patient with psoriasis who fulfills the inclusion and exclusion criteria was selected as study population. After taking written consent proper history and clinical examination was done. The parameters included were age at onset of disease, age at first treatment, current age, sex, type of disease and distribution of lesions. After data collection and processing all statistical analysis was done by SPSS software version 26. p value <0.05 was considered as significant. Result: The mean age was found 35.15±13.63 with the range of 18-70 years. Female are more common than male. Male and female ratio was 1:1.2. Mean age of onset of disease was 32.15+12.28 with the range of 13-70 years. Mean duration of disease was 2.65+2.76. Regarding severity of psoriasis according to PASI score, 45 (56.3%) patients had mild psoriasis (PASI ≤10) and 35 (43.8%) had moderate to severe psoriasis (PASI >10). Conclusion: Psoriasis is a common dermatological disease accounting 2.9% of all dermatology patients in our country. The disease is more frequent in the third decade of life and has a male predominance in our region. Treatment compliance has been found to be poor. In the current study, we observed mild psoriasis is a predominant pattern assessed by PASI score. J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 26-30